2008
DOI: 10.1128/aem.00812-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Endoglucanase Belonging to a New Subfamily of Glycoside Hydrolase Family 45 of the BasidiomycetePhanerochaete chrysosporium

Abstract: The wood decay fungus Phanerochaete chrysosporium has served as a model system for the study of lignocellulose conversions, but aspects of its cellulolytic system remain uncertain. Here, we report identifying the gene that encodes the glycoside hydrolase (GH) family 45 endoglucanase (EG) from the fungus, cloning the cDNA, determining its heterologous expression in the methylotrophic yeast Pichia pastoris, and characterizing the recombinant protein. The cDNA consisted of 718 bp, including an open reading frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 51 publications
6
74
0
6
Order By: Relevance
“…4B and 5C). AfSwo1 is distantly related to family 45 endoglucanases, as shown in the phylogenetic tree of Igarashi et al (9). These investigators reported that cellulosic suspensions were dispersed when they were incubated with Phanerochaete chrysosporium family 45 endoglucanase PcCel45C.…”
Section: Nidulans a Niger A Oryzae A Flavus A Clavatus A Tementioning
confidence: 90%
“…4B and 5C). AfSwo1 is distantly related to family 45 endoglucanases, as shown in the phylogenetic tree of Igarashi et al (9). These investigators reported that cellulosic suspensions were dispersed when they were incubated with Phanerochaete chrysosporium family 45 endoglucanase PcCel45C.…”
Section: Nidulans a Niger A Oryzae A Flavus A Clavatus A Tementioning
confidence: 90%
“…Shodex KS-801 and KS-802 (Showa Denko K.K., Kanagawa, Japan) columns operated at 80°C with a flow rate of 0.6 ml/min. Hydrolysis products were also viewed on thin-layer chromatography (TLC) by using silica gel 60 TLC sheets (Fisher), following protocols described previously (27). EtOAc-CH 3 COOH-H 2 O (3:2:1 by volume) was used to develop the TLC plates; reducing sugars were detected by the orcinol reagent (1% orcinol in 10% H 2 SO 4 dissolved in ethanol).…”
Section: Methodsmentioning
confidence: 99%
“…The culture supernatant was boiled for 5 min to inactivate enzymes secreted by the fungus. The concentrations of glucose and cellooligosaccharides in the supernatant were measured by high-performance liquid chromatography (HPLC; LC-2000 series; Jasco, Tokyo, Japan), using a corona-charged aerosol detector (ESA Biosciences, Chelmsford, MA) based on our previous report (21). The supernatants were filtered using a MultiScreen HTS 96-well filtration system (Millipore Corporation, Billerica, MA) and then separated on a Shodex Asahipak NH2P-50 4E (Showa Denko K.K., Kanagawa, Japan) with isocratic elution (65% acetonitrile, 35% H 2 O [vol/vol]).…”
Section: Methodsmentioning
confidence: 99%